Mobile services adoption in a hospitality consumer context - Rita, P.; Oliveira, T.; Estorninho, A.; Moro, S. (International Journal of Culture, Tourism, and Hospitality Research, 2018)
Purpose: This study presents a model drawn on both the extension of the unified theory of acceptance and use of technology (UTAUT2) and the perceived value for explaining consumer behavior toward mobile hospitality services (MHS) from two perspectives: intention to use and recommendation. Design/methodology/approach: The partial least square (PLS) was applied to data gathered from 348 validated responses to a survey in order to test a number of research hypotheses. Findings: Results found that the proposed conceptual model explains 62% of the intention to use MHS, and 51% of the variation in recommendation. Perceived value plays a role in explaining both the intention to use and recommend MHS, with both constructs also helping in explaining behavior intention, to which effort expectancy facilitating conditions and performance expectancy also contribute. Originality/value: This research goes beyond perceived value by combining it with a cornerstone model used in technology adoption studies, the UTAUT2. The paper addresses updated mobile hospitality services that include but are not limited to mobile hotel reservations.